SYSTEMATIC LITERATURE REVIEW (SLR): PEMBERDAYAAN PEREMPUAN BAGI PENGEMBANGAN PROGRAM YANG ADA DI INDONESIA - Sari, Intan Devi Orlita; Latifah, Luluk; Ritonga, Iskandar (Kafa`ah: Journal of Gender Studies, 2024)
Women's empowerment plays an important role in gender equality through economic development. This study aims to determine women's empowerment for program development in Indonesia. With a systematic review paradigm approach in journals published from 2007 to 2021. This study uses a Systematic Literature Review (SLR) approach with data sources from indexed journal literature with ISSN. Data collection was done by surfing the internet using Google Scholar. The population of research data uses 25 index journals from various journal publishers. The results obtained are a) program development paying attention to the position and role of women's strategies in poverty alleviation, b) fulfillment of women's rights socially and economically, c) increasing women's education life skills, d) increasing women's empowerment competencies, through theoretical and practical aspects, e) program development can be improved socially and economically.